PENGARUH LIFESTYLE DAN LOCAL FOOD TERHADAP PEMILIHAN DESTINASI WISATA DI KOTA BUKITTINGGI - Suci Agusti Wulandari; Verinita; Suziana (Halu Oleo University, 2025)
This study aims to analyse the influence of lifestyle and local food on the selection of Bukittinggi as a tourist destination. The research employs Structural Equation Modelling (SEM) using SmartPLS 4.0 software with a sample of 213 domestic tourists from outside West Sumatra Province and not of Minangkabau ethnicity. The results show that both lifestyle and local food significantly influence the selection of a tourist destination. In other words, a destination is more likely to be chosen when there is alignment between tourists' lifestyles and the destination’s characteristics, along with authentic and accessible local food offerings. Therefore, it is necessary to develop innovative promotional strategies and improve the quality of local food presentation to increase tourist interest in visiting Bukittinggi and recommending it to others.